2017
DOI: 10.1371/journal.pone.0175820
|View full text |Cite
|
Sign up to set email alerts
|

Effects of over-expressing a native gene encoding 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) on glyphosate resistance in Arabidopsis thaliana

Abstract: Widespread overuse of the herbicide glyphosate, the active ingredient in RoundUp®, has led to the evolution of glyphosate-resistant weed biotypes, some of which persist by overproducing the herbicide’s target enzyme, 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS). EPSPS is a key enzyme in the shikimic acid pathway for biosynthesis of aromatic amino acids, lignin, and defensive compounds, but little is known about how overproducing EPSPS affects downstream metabolites, growth, or lifetime fitness in the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…In addition, we did not find significant differences in fitness-related traits between the EV and parental lineages. These results support previous findings that enhanced fitness/fecundity (as shown in (Su et al, 2008 ; Wang et al, 2014 ; Yang et al, 2017a ),b) is not the consequence of an insertion or position effect (process of transgenesis), but due to the action of the transgene itself. We therefore confirm that overexpression of EPSPS in GE plants with a proper level can result in overproduction of their EPSPS and increased glyphosate tolerance.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In addition, we did not find significant differences in fitness-related traits between the EV and parental lineages. These results support previous findings that enhanced fitness/fecundity (as shown in (Su et al, 2008 ; Wang et al, 2014 ; Yang et al, 2017a ),b) is not the consequence of an insertion or position effect (process of transgenesis), but due to the action of the transgene itself. We therefore confirm that overexpression of EPSPS in GE plants with a proper level can result in overproduction of their EPSPS and increased glyphosate tolerance.…”
Section: Discussionsupporting
confidence: 92%
“…Increased tolerance to glyphosate in our transgenic plants overexpressing an EPSPS gene is presumably due to the sufficiently surplus EPSPS that can bind glyphosate (Rogers et al, 1983 ), as reported in P. hybrida (Shah et al, 1986 ), tobacco plants (Jones et al, 1996 ), and Arabidopsis (Klee et al, 1987 ; Yang et al, 2017a ). Thus, these results confirm the strategy of overproducing EPSPS driven by a strong promoter (e.g., pCaMV35S for dicots and pUbiquitin for monocots) to be effective in increase GE crops' tolerance to glyphosate, regardless of exogenous (as in this study) or endogenous (Klee et al, 1987 ; Su et al, 2008 ; Yang et al, 2017a ). The application of an endogenous transgene overproducing EPSPS at a proper level to develop GE glyphosate-tolerant crops may have particular commercial values.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…It is difficult to explain why the EPSPS protein from petunia and chile which share ~90% sequence similarity show differences in glyphosate-resistance but we cannot rule out the possibility that the EPSPS protein from this petunia cell line was resistant to glyphosate, notwithstanding that this line was deemed resistant due to EPSPS gene amplification (36). More recently, it has been shown that Arabidopsis plants transformed with an Arabidopsis EPSPS gene driven by the CaMV35S promoter was tolerant to glyphosate [ 37 ]. In another study, it was shown that a an EPSPS gene from Convolvulus arvensis driven by the CaMV35S promoter also conferred resistance to glyphosate in Arabidopsis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%